Medullary Serotonergic Binding Deficits and Hippocampal Abnormalities in Sudden Infant Death Syndrome: One or Two Entities? - Haynes, Robin L.; Kinney, Hannah C.; Haas, Elisabeth A.; Duncan, Jhodie R.; Riehs, Molly; Trachtenberg, Felicia; Armstrong, Dawna D.; Alexandrescu, Sanda; Cryan, Jane B.; Hefti, Marco M.; Krous, Henry F.; Goldstein, Richard D.; et al. (Frontiers in Pediatrics, 2021)
Sudden infant death syndrome (SIDS) is understood as a syndrome that presents with the common phenotype of sudden death but involves heterogenous biological causes. Many pathological findings have been consistently reported in SIDS, notably in areas of the brain known to play a role in autonomic control and arousal. Our laboratory has reported abnormalities in SIDS cases in medullary serotonin (5-HT) receptor 1A and within the dentate gyrus of the hippocampus. Unknown, however, is whether the medullary and hippocampal abnormalities coexist in the same SIDS cases, supporting a biological relationship of one abnormality with the other. In this study, we begin with an analysis of medullary 5-HT1A binding, as determined by receptor ligand autoradiography, in a combined cohort of published and unpublished SIDS (n=86) and control (n=22) cases. We report 5-HT1A binding abnormalities consistent with previously reported data, including lower age-adjusted mean binding in SIDS and age vs. diagnosis interactions. Utilizing this combined cohort of cases, we identified 41 SIDS cases with overlapping medullary 5-HT1A binding data and hippocampal assessment and statistically addressed the relationship between abnormalities at each site. Within this SIDS analytic cohort, we defined abnormal (low) medullary 5-HT1A binding as within the lowest quartile of binding adjusted for age and we examined three specific hippocampal findings previously identified as significantly more prevalent in SIDS compared to controls (granular cell bilamination, clusters of immature cells in the subgranular layer, and single ectopic cells in the molecular layer of the dentate gyrus). Our data did not find a strong statistical relationship between low medullary 5-HT1A binding and the presence of any of the hippocampal abnormalities examined. It did, however, identify a subset of SIDS (~25%) with both low medullary 5-HT1A binding and hippocampal abnormalities. The subset of SIDS cases with both low medullary 5-HT1A binding and single ectopic cells in the molecular layer was associated with prenatal smoking (p=0.02), suggesting a role for the exposure in development of the two abnormalities. Overall, our data present novel information on the relationship between neuropathogical abnormalities in SIDS and support the heterogenous nature and overall complexity of SIDS pathogenesis.